2007
DOI: 10.1007/s12013-007-0034-5
|View full text |Cite
|
Sign up to set email alerts
|

Femtochemistry in enzyme catalysis: DNA photolyase

Abstract: Photolyase uses light energy to split UV-induced cyclobutane pyrimidine dimers in damaged DNA. This photoenzyme encompasses a series of elementary dynamical processes during repair function from early photoinitiation by a photoantenna molecule to enhance repair efficiency, to in vitro photoreduction through aromatic residues to reconvert the cofactor to the active form, and to final photorepair to fix damaged DNA. The corresponding series of dynamics include resonance energy transfer, intraprotein electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 84 publications
(122 reference statements)
2
37
0
Order By: Relevance
“…A, the Trp triad. The arrows show the two pathways of photoreduction (16,17); that is, electron hopping through the Trp triad and electron tunneling through ␣-helix 15 and Phe-366. The Trp triad residues in Type 1 CRYs that correspond to the E. coli Trp triad and which were mutated in this study are indicated in parentheses.…”
Section: Purification Of Insect Typementioning
confidence: 99%
“…A, the Trp triad. The arrows show the two pathways of photoreduction (16,17); that is, electron hopping through the Trp triad and electron tunneling through ␣-helix 15 and Phe-366. The Trp triad residues in Type 1 CRYs that correspond to the E. coli Trp triad and which were mutated in this study are indicated in parentheses.…”
Section: Purification Of Insect Typementioning
confidence: 99%
“…CPD can be completely restored by a photoenzyme, photolyase, through absorption of visible blue light (4). In our early work (5-7), we have observed a cyclic electron-transfer (ET) reaction in thymine dimer (ThiT) repair by photolyase and determined the time scale of 700 ps for the complete repair photocycle (7). However, the central questions of whether the splitting of the cyclobutane ring is synchronously or asynchronously concerted or stepwise and whether the cyclic ET involves specific tunneling pathways were not resolved.…”
mentioning
confidence: 99%
“…Thus, upon excitation the local polar environments of these function sites would proceed to a series of relaxations. Understanding of these local motions is crucial to their functional dynamics of resonance energy transfer from the photoantenna to the cofactor and electron transfer between the cofactor and the substrate in catalytic repair photocycle.Our earlier studies on Escherichia coli CPD photolyase (EcPhr) showed that the active-site solvation is on the similar time scale of the catalytic reaction of electron transfer in hundreds of picoseconds, resulting in a nonequilibrium dynamic process and a direct modulation of charge separation (10,(27)(28)(29). The characterization of resonance energy transfer from the photoantenna (30, 31) revealed minor solvation at the binding site in less than 20 ps.…”
mentioning
confidence: 99%
“…Our earlier studies on Escherichia coli CPD photolyase (EcPhr) showed that the active-site solvation is on the similar time scale of the catalytic reaction of electron transfer in hundreds of picoseconds, resulting in a nonequilibrium dynamic process and a direct modulation of charge separation (10,(27)(28)(29). The characterization of resonance energy transfer from the photoantenna (30, 31) revealed minor solvation at the binding site in less than 20 ps.…”
mentioning
confidence: 99%